Mental health among pregnant women with COVID‐19–related stressors and worries in the United States. Issue 4 (19th May 2021) - Liu, Jihong; Hung, Peiyin; Alberg, Anthony J.; Hair, Nicole L.; Whitaker, Kara M.; Simon, Jessica; Taylor, Sherri K.
Abstract: Background: Few studies have evaluated whether pandemic‐related stressors, worries, and social distancing have affected the mental health of pregnant women during the COVID‐19 pandemic. Methods: Data came from an online survey of United States pregnant women (n = 715), conducted in May 2020. The Edinburgh Postnatal Depression Scale and Generalized Anxiety Disorder Scale were used to assess depressive symptoms, thoughts of self‐harm, and moderate or severe anxiety. Multiple logistic regressions were used to examine the associations of COVID‐19 experiences with mental health outcomes. Results: Participants were racially diverse. The prevalence of adverse mental health outcomes was 36% for probable depression, 20% for thoughts of self‐harm, and 22% for anxiety. Women who reported family members dying from COVID‐19 had four times higher odds of having thoughts of self‐harm than women who did not experience family death. Depression was more prevalent among women who canceled or reduced medical appointments. Women were more likely to have worse mental health outcomes if they expressed worry about getting financial or emotional/social support, about their pregnancy, or about family or friends. Strict social distancing was positively associated with depression. A higher proportion of adults working from home was inversely associated with depression and thoughts of self‐harm. Conclusion: High percentages of pregnant women had symptoms of depression or anxiety, suggesting an urgent need to screen and treat mental health conditions among pregnant women during the pandemic. Pandemic‐related risks and protective factors are relevant to developing tailored interventions to address the mental health of pregnant women during pandemic circumstances.